Identifying Strategies to Cope with Mental Illness-related Stigma of Family Caregiver Living with Mental Illness in Pamekasan, Indonesia: A Qualitative Study - Willi Holis; Ah. Yusuf; AV Sri Suhardiningsih (Alta Dharma Publisher, 2020)
The social stigma that experienced by people with mental illness has negative consequences both for the patients and their family members. The stigma causes psychological stress, such as depression, frustration, and anxiety for the family. The study aimed to explore the family members’ efforts to cope with mental illness stigma in social encounters. This study was qualitative. Eleven families were living with mental illness who were experiencing stigma, and data were collected mainly through in-depth interviews. The results of this study reported that families were using different coping strategies to counter the stigma. They used Problem-focused coping and emotional focused dealing. Adaptive coping strategies used by families of people with mental illness can help to reduce psychological stress. In contrast, coping strategies that tend to be maladaptive can increase the occurrence of psychological stress. Families of people with mental illness that affected by stigma must get psychological therapy to improve the quality of life, and to reduce the negative impact of the stigma itself